2016
DOI: 10.1002/ajmg.a.37994
|View full text |Cite
|
Sign up to set email alerts
|

Sudden infant death “syndrome”—Insights and future directions from a Utah population database analysis

Abstract: Sudden Infant Death syndrome" (SIDS) represents the commonest category of infant death after the first month of life. As genome scale sequencing greatly facilitates the identification of new candidate disease variants, the challenges of ascribing causation to these variants persists. In order to determine the extent to which SIDS occurs in related individuals and their pedigree structure we undertook an analysis of SIDS using the Utah Population Database, recording, for example, evidence of enrichment for gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…7,8 Genetic contributions to SUDP are supported by studies of families whose children died from SIDS during the "safe sleep" era, which showed an increased risk for recurrence in subsequent siblings (odds ratio, [OR], 4.2) and within 3 generations (OR, 9.3). 9 The prevailing etiologic model of SUDP postulates that modest extrinsic threats become fatal in infants and children who harbor intrinsic vulnerabilities. 10 Early research described intrinsic vulnerabilities as biologically mediated risk factors such as prematurity, male sex, and prenatal alcohol and/or tobacco exposure.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Genetic contributions to SUDP are supported by studies of families whose children died from SIDS during the "safe sleep" era, which showed an increased risk for recurrence in subsequent siblings (odds ratio, [OR], 4.2) and within 3 generations (OR, 9.3). 9 The prevailing etiologic model of SUDP postulates that modest extrinsic threats become fatal in infants and children who harbor intrinsic vulnerabilities. 10 Early research described intrinsic vulnerabilities as biologically mediated risk factors such as prematurity, male sex, and prenatal alcohol and/or tobacco exposure.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the lingering influence of "Meadow's Law" (89) impedes the discovery of genetic diseases. Familial recurrence studies generate odds ratios of 4.84 for SIDS and other or unknown deaths to sibs at any age or an odds ratio of 9.29 (CI 2.62-32.96) in first through third degree relatives (90). Effects of this magnitude are typically seen with Mendelian disorders or conditions with directly causal environmental influences.…”
Section: A New Hypothesismentioning
confidence: 99%